"Satisfaction lies in the effort". Is Gandhi's quote also true for satisfaction with commuting?. (September 2021) - Van Acker, Veronique; Ho, Loan; Mulley, Corinne
Abstract: Research on travel satisfaction in terms of its determinants and in terms of its relationship with subjective well-being has not taken account of the effort in travelling. This paper explicitly considers the role of effort and its three constituent elements (physical, cognitive and affective) by analysing the way each interacts with travel satisfaction and subjective well-being. The context of the study is Greater Sydney, New South Wales, Australia where respondents answered an internet-based survey. The paper has two main objectives. First to explore the benefit or otherwise of including 'effort' in analyses of travel satisfaction: the analysis shows that including effort provides additional explanation. Second, to explore the bidirectional nature of the interaction between travel satisfaction and subjective well-being. The analysis suggests that the bottom-up approach to well-being whereby the link is from travel satisfaction to well-being is stronger. The paper concludes with some policy implications of how transport policy can reduce effort and thereby make sustainable travel more appealing.